Parenting in South American and African Contexts - Lucia Seidl-de-Moura, Maria (IntechOpen, 2013)
Parenting involves a set of values, beliefs and practices of child care that create a developmental context and vary from culture to culture. Studies about parenting are of fundamental importance to the understanding of human development. This book has nine chapters and it addresses parenting and child care in two South American countries (Brazil and Colombia) and four African ones (Cameroon, Ghana, Liberia and Nigeria). It aims at contributing to the knowledge about human development in contexts of the majority world, not often considered in the psychological literature. Besides bringing data from different countries, it focuses in diverse scenarios in Brazil. The data and discussions include mothers, fathers and grandmothers beliefs and/or practices, parental styles and intervention programs oriented to quality parental care.